LEGAL STATUS OF BIOETHICS: INTERNATIONAL EXPERIENCE AND NATIONAL CHARACTERISTICS - Baksheev, Andrei; Turchina, Zhanna; Galaktionova, Marina; Gusarenko, Victoria; Rakhinsky, Dmitry; Shepeleva, Julia (Revista Inclusiones, 2020)
The work presented explores the legal status of bioethics. In the modern world of scientific and technological progress, ethical norms are becoming increasingly important in order to reduce the negative impact on human life and health of certain factors arising from scientific and technological progress. To a large extent, this applies to medical activities, and in particular to their special direction - biomedicine. Current bioethical norms are considered in the work. Authors investigate the Russian legislation, the legislation of foreign countries, international legal norms regulating the right of the personality for health protection, anyway connected with bioethics. The views of authors - the brightest representatives of domestic and foreign science, on the essence of bioethics and its relationship with law are given.